Congenital coronary artery anomaly simulating a ventricular septal defect. (November 2015) - Azari, Ali; Moravvej, Zahra; Fazlinezhad, Afsoon; Bigdelu, Leila
Anomalous origin of the circumflex artery of the right sinus of Valsalva is a rare finding which may be present with other cardiac malformations. A 19-year-old man presented with syncope. A transthoracic echocardiogram revealed discrete subaortic stenosis with a small defect just below the aortic valve, suggesting a ventricular septal defect. Transesophageal echocardiography showed anomalous origin of the circumflex artery from the right sinus of Valsalva. This was confirmed by coronary angiography. The patient underwent successful web resection without concomitant coronary surgery. Failure to demonstrate a coronary artery anomaly can be misleading for surgeons and perilous for patients.